Phospholipase D (PLD) 1 and 2 expression in ABC cells, a new retinal pigment epithelium cell line - Bermúdez, Vicente (2021)
The retinal pigment epithelium (RPE) plays critical roles in the correct function of the neural retina and photoreceptor survival. Classical phospholipases D (PLD1 and 2) hydrolyze phosphatidylcholine (PC) to generate phosphatidic acid (PA) and choline. PA can be further dephosphorylated to diacylglycerol (DAG) by lipid phosphate phosphatases (LPPs). DAG and PA, as bioactive lipids, can modulate the activity of various proteins involved in cell signaling events, such as protein kinases C and the mTOR (mammalian target of rapamycin) complex, among others. Our previous studies demonstrated for the first time the participation of classical PLDs in the inflammatory response and in the autophagic process of RPE (ARPE-19 and D407) cells exposed to lipopolysaccharide (LPS). The aim of the present work was to study PLD1 and PLD2 expression in a new human RPE cell line (ABC cells), spontaneously arisen from a primary RPE cell culture. Western blot assays (WB) show that both classical PLDs are expressed in ABC cells. Using PLD1 and PLD2 siRNA, we were able to partially decrease the expression of PLD1 (by 42%) and PLD2 (by30 %). Since PLD-generated PA activates mTORC1, the main inhibitor of autophagy initiation, we wanted to study the effect of classical PLDs silencing on mTOR activation. For this purpose, WB assays were performed in order to study the mTOR downstream effector S6 kinase (S6K) activation (phosphorylation) in ABC cells transfected with PLD1 and PLD2 siRNA. Our results show that in ABC cells transfected with PLD1 and PLD2 siRNA S6K activation is reduced by 34%. This result is in accordance with the increased autophagic process induced by PLD1 and PLD2 pharmacological inhibitors, previously observed in D407 RPE cells. Since it was previously demonstrated that the PLD pathway can modulate the phagocytic process in macrophages, we wanted to evaluate the effect of PLD1 and PLD2 silencing on the photoreceptor outer segment (POS) phagocytic process in ABC cells. With this aim, ABC cells were incubated with POS for 16 h, and total (bound + internal) and internalized POS were measured by WB using an anti-rhodopsin antibody. Under basal conditions, PLD1 and PLD2 silencing seem not to significantly affect POS phagocytosis by ABC cells. In conclusion, our results demonstrate the expression of classical PLD isoforms in a new RPE cell line and their role in the modulation of the mTOR/S6K pathway. Further experiments are needed to fully elucidate the role of classical PLDs in the phagocytic process of ABC RPE cells exposed to inflammatory conditions. The results presented herein, together with our previous findings, contribute to the knowledge of the molecular basis of retinal inflammatory and degenerative diseases, such as diabetic retinopathy, aged-related macular degeneration and endophthalmitis, among others.